Science Alone Won’t Do It! South Africa’s Endangered Humpback Dolphins Sousa plumbea Face Complex Conservation Challenges - Plön, Stephanie; Atkins, Shanan; Cockcroft, Vic; Conry, Danielle; Dines, Sasha; Elwen, Simon; Gennari, Enrico; Gopal, Keshni; Gridley, Tess; Hörbst, Sandra; James, Bridget S.; Penry, Gwenith; et al. (Frontiers in Marine Science, 2021)
The Indian Ocean humpback dolphin (Sousa plumbea) is “endangered” with likely less than 500 animals remaining in South African waters. Established in 2016, the SouSA Consortium is a formalised network of scientists and conservationists to combine knowledge and research efforts, and make coordinated decisions with the aim of conserving the species. The first collaborative project collated available photo-identification data in an attempt to refine a national population estimate and investigate movements between research sites. This work was able to identify 250 uniquely marked individuals, with the population divided into the south-coast (Agulhas bioregion) and east-coast (Natal bioregion) populations. Environmental factors almost certainly play a role in the declining numbers of the species in South African waters. However, individual threats and solutions are challenging to identify as the South African marine environment is undergoing significant natural and anthropogenic changes with major shifts in the distribution and numbers of some prey, competitor and predator species. Therefore, we believe that a continued investigation of potential contributing factors and their interaction will take too long, inevitably resulting in another case of documenting extinction. With this in mind, we present the results of a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis in an effort to help us identify the next steps to take toward the conservation of humpback dolphins in South African waters. We unanimously conclude that no single cause for the rapid decline of humpback dolphins in South African waters can be identified, and that the cumulative effects of multiple stressors, which are difficult to pinpoint and mitigate, are impacting population numbers. While highlighting the need for continued research, we suggest a shift toward more action-focused conservation efforts, the first concrete steps being the development of a Conservation Management Plan with input from other stakeholders.